2021
DOI: 10.3389/fpls.2021.678295
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous 2,4-Epibrassinolide Treatment Maintains the Quality of Carambola Fruit Associated With Enhanced Antioxidant Capacity and Alternative Respiratory Metabolism

Abstract: Brassinosteroids act by delaying fruit ripening. The effects of different concentrations of 2,4-epibrassinolide (eBL) treatments on carambola fruit ripening were investigated. The results show that treatment of 2.8 mg L–1, eBL with 10 min effectively delays ripening and maintains the quality of carambola fruit. This is achieved by retarding color changes and firmness losses while maintaining high level of soluble protein content and vitamin C, and low organic acid content. eBL-delayed senescence may be due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…Apart from DAA 40 and DAA 50, exogenous EBR treatment considerably enhanced the content of soluble and reducing sugars. Similarly, Zhu et al (2021) found that exogenous application of 2,4-EBR treatment promoted the accumulation of sugars in carambola during the late fruit ripening stage. Nevertheless, under exogenous JA treatment, we observed that soluble sugar contents declined at DAA 40 and DAA 50 (a decrease of 2.37% and 8.74% than the control group, respectively) while reducing sugar contents decreased at DAA 60, 70, and 80 (a decline of 9.07%, 7.85% and 10.90% than the control group, respectively).…”
Section: Sugars Biosynthesis Metabolism and Transportationmentioning
confidence: 74%
See 1 more Smart Citation
“…Apart from DAA 40 and DAA 50, exogenous EBR treatment considerably enhanced the content of soluble and reducing sugars. Similarly, Zhu et al (2021) found that exogenous application of 2,4-EBR treatment promoted the accumulation of sugars in carambola during the late fruit ripening stage. Nevertheless, under exogenous JA treatment, we observed that soluble sugar contents declined at DAA 40 and DAA 50 (a decrease of 2.37% and 8.74% than the control group, respectively) while reducing sugar contents decreased at DAA 60, 70, and 80 (a decline of 9.07%, 7.85% and 10.90% than the control group, respectively).…”
Section: Sugars Biosynthesis Metabolism and Transportationmentioning
confidence: 74%
“…Exogenous EBR increased TSS content in carambola fruit (Zhu et al, 2021), and JA stimulated ripening, anthocyanins formation, and the volatilization of hexanol, linalool, and aterpineol in peach fruit (Wei et al, 2017). Additionally, exogenous EBR treatment increased the activity of several lipid peroxidation and defense-related enzymes, which maintained the firmness of grape berries at a greater level and reduced the rate of fruit drop and decay (Liu et al, 2016).…”
Section: Biochemical Propertiesmentioning
confidence: 89%
“…It has also been reported that the application of exogenous GA inhibited fruit softening and delayed the loss of ascorbic acid and soluble reducing sugar, thereby prolonging the shelf life of banana fruit ( Huang et al., 2014 ). Recently, in carambola fruit, exogenous 2,4-epibrassinolide treatment maintained fruit quality and inhibited fruit ripening due to the increase in levels of IAA and GA in carambola fruit ( Zhu et al., 2021 ). Therefore, taken together, we could conclude that HRW treatment delayed senescence and extended the shelf life of postharvest okras also due to the increase of levels of GA and IAA.…”
Section: Discussionmentioning
confidence: 99%
“…Whether such response primes the activation of a fruit's antioxidant system, when chilling stress is initiated, is unknown. Another mechanism that has been related to BR‐induced stress tolerance, studied initially in whole plants (Wei et al, 2015) and more recently in harvested fruit (Zhu et al, 2021), is the induction of the alternative oxidase (AOX) pathway. The fact that the application of the alternative oxidase inhibitor salicylhydroxamic acid (SHAM) decreased plant stress tolerance suggests that mitochondrial acclimation was necessary for the beneficial effects induced by BRs (Hu et al, 2019; Wei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%